AKUNTANSI LINGKUNGAN SEBAGAI STRATEGI PENGELOLAAN LINGKUNGAN DAERAH WISATA GUNUNG IJEN KABUPATEN BANYUWANGI - Izzato Millati (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2016)
The purpose of this study was to explore the Environmental Accounting as a management strategy of the Mount Ijen. The Mount Ijen is a tourism icon that has been recognized by the international community because of natural potentials that exist at the Mount Ijen, however, with increasing image ijen Internationally it also increases the number of tourists who visit the Mount Ijen, be it tourists in domestic and foreign. Increasing the number of tourists also have an impact, be it positive or negative impact. So it needs proper management so Ijen volcano could become sustainable natural tourist areas. This study uses a qualitative method by collecting data through interviews, observation and collection of related documents, and then analyzed using SWOT analysis, so that can know the strengths, weaknesses, opportunities, and threats. The results of this research is to know that environmental accounting is an appropriate strategy in the management of the Mount Ijenenvironment.Keyword : Environmental Accounting, tourism, strategy